The Analysis of Students Politeness Response on Lecturer Request by Voice Message in WhatsApp Group at Fifth Semester of TBI 2021 IAIN Madura Based on Brown and Levinson Perspective - Raudhatil Jannah; Abd. Ghofur (Institut Agama Islam Negeri Madura, 2022)
Language is used for communication to convey one's intention to each other in social interaction. From the language, someone has a different ways to speak with the other people, such as someone speaks with their parent, their friend, their teacher and so on. With a different partner to communicate, people do the different way to speak in every aspect, especially in politeness aspect. In this thesis, the researcher uses the sample of every class of fifth semester of TBI 2021IAIN Madura as a subject. The researcher researches about politeness response by voice message of the subject. The focus of the study is what is the types of politeness used and analyzing how are the politeness used by students of fifth semester of TBI 2021IAIN Madura in response lecturer request by voice message in WhatsApp group based on Brown and Levinson perspective. Then, the objective of this research is to analyze the types of politeness to know the politeness used by students of fifth semester of TBI2021 IAIN Madura in response lecturer request by voice message in Whatsapp group based on Brown and Levinson perspective. The approach of this study is qualitative approach and uses content analysis. The kind of this research is library research. The data is taken from voice message in Whatsapp group. Then, the researcher collects the data through the observation and documentation and analyze the data which use politeness strategy.The result of this research is there are three types of politeness available in the WhatsApp group of fifth semester of TBI 2021 IAIN Madura based on Brown and Levinson perspective. They are positive politeness, negative politeness and off record. While bald on record is not available in this research because the use of bald off record is usually used for close friend and family. The use of sub politeness also known by the utterance that used of fifth semester of TBI 2021 IAIN Madura, such as the use of be incomplete and give hints or clue of off record, assert or presuppose speaker’s knowledge of and concern for hearer’s wants of positive politeness and minimize the size of imposition of negative politeness. Most of students use positive politeness in responding the lecturer.